Analisis Kekerabatan Genetik Kultivar Kopi Arabika Berbuah Kuning dan Berbuah Merah Berdasarkan Marka SSR - Nur Kholilatul Izzah; Enny Randriani; Dani Dani (Jurnal Tanaman Industri dan Penyegar, 2015)
Yellow berry of Arabica coffee (AGK-1) cultivated in Garut is a local cultivar that potentially could be released as a superior variety. However, its genetic background has not been studied. Information of genetic background is one of the requirement in releasing of a new variety. The objective of this research was to analyze the genetic relationships of AGK-1 cultivar with 11 red berries Arabica coffee cultivars based on simple sequence repeats (SSR) markers to find polymorphisms and clustering. The research was carried out at the Molecular Laboratory of Indonesian Industrial and Beverage Crops Research Institute and Biology Molecular Laboratory of Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development, from January to March 2015. These twelve Arabica coffee cultivars were obtained from Garut Regency. A total of 12 SSR primers were used to investigate the genetic relationships of the plant. The result showed that 12 SSR markers were adequate to identify the relationships among 12 Arabica coffee cultivars. The genetic clustering obtained in this study is related to plant morphology, particularly plant growth characters, such as tall, semi dwarf and dwarf. AGK-1 cultivar genetically related to ABP-2, one of red berries cultivars that originated from Brazil. Both of these cultivars have the same growing type characters (i.e. semi dwarf). AGK-1 cultivar that has yellow berry color presumably derived from an open pollinated red berries parents, mainly ABP-2 cultivar. Therefore, AGK-1 is a unique cultivar that could be released as a local superior variety.